Inquisition in Chile: A Historiographical Journey and New Study Proposals - Cordero Fernández, Macarena (2019)
In 1570 the Spanish Crown decided to create, in the overseas spaces, the Holy Office of the Inquisition in order to control, effectively, the religious manifestations of the people and their social behaviors, bringing intolerance towards those who had different practices. However, initially it had only two district courts installed in the viceroyalties capitals of Mexico and Peru. The other places, captaincies and governorates, were controlled by commissioners dependent on Mexico or Lima, as appropriate. In the case of the Government of Chile, several police stations were deployed between the two dioceses. However, they were not efficient enough to achieve the objectives proposed in the inquisitorial ideology, on the one hand because of precarious material, and on the other hand because of the lack of ad-hoc officials to fill the positions. This led to the Chilean Governorate experience a more laxed control than other imperial territories. However, the climate of fear and prejudice among the inhabitants permeated the society generating intolerance and discrimination through other perspectives and through other social control devices, which survived in the republic and allow to understand —partway— the intolerance and discrimination in the current Chile. The present article will make a tour of the installation of the Holy Office in America, the historiographic status of the studies related to the Inquisition in Chile, the possible lines of investigation and the hypotheses to be tested.